Implementation of Personality Tests in the Learning Process in Era 4.0 Based on the Concept of Pumping HR Model for the world of Education in Indonesia - Ramly, Amir Tengku (Jurnal Manajemen, 2022)
Understanding the character of learning is one of the important factors for success in learning and in the future. The era of 4.0 and the COVID-19 pandemic today has forced major changes in the teaching and learning system so that it is not disruptive. The learning process in the 4.0 era requires all-digital and effective breakthroughs. This condition is also supported by the COVID-19 pandemic which is predicted not to end soon. This study aims to (1) design a digital student character understanding test tool (2) develop students through a character approach to learning the Pumping HR Model concept, (3) develop teaching-learning techniques based on student character development through strengthening personality, competence and values. - spirituality values. The research method used is a qualitative study of literature and evaluation of the test equipment used for decades. The results of the study indicate that the implementation of personality tests (behavior and character) in the learning process in the 4.0 era greatly determines the effectiveness of the teaching and learning process. This effectiveness is strongly influenced by the implementation of three main components, namely (1) teacher integrity, (2) teacher competence, and (3) teacher personality in teaching, as part of the Pumping-HR Model framework.